A forgotten navy: fish, fishermen, fishing vessels and the Great War at sea. (2nd January 2017) - Robinson, Robb
ABSTRACT: Discussion about the Great War at sea tends to centre on capital ships and Jutland. Far less has been written about the crucial role played by fishermen, fishing vessels and their coastal communities. Yet armed fishing vessels and their fishermen crews were continually on the maritime front line. They formed the backbone of the Auxiliary Patrol, working principally on anti-U-boat patrols or minesweeping. Around 3000 fishing vessels were requisitioned whilst more than 39, 000 fishermen joined the Trawler Section of the Royal Naval Reserve. The cultural, social and attitudinal gulf between working fishermen and many RN officers was enormous. Those vessels left fishing also played a vital role in maintaining the food supplies; many were sunk whilst working. Around 672 fishing vessels were lost through enemy action whilst either fishing or on Admiralty service. After the war, their substantial role was gradually forgotten, now hardly recognised. This paper examines their contribution.